Healing and Angiogenic Properties of Collagen/Chitosan Scaffolds Enriched with Hyperstable FGF2-STAB® Protein: In Vitro, Ex Ovo and In Vivo Comprehensive Evaluation - Vojtová, Lucy; Pavliňáková, Veronika; Muchová, Johana; Kacvinská, Katarína; Brtníková, Jana; Knoz, Martin; Lipový, Břetislav; Faldyna, Martin; Göpfert, Eduard; Holoubek, Jakub; Pavlovský, Zdeněk; Vícenová, Monika; et al. (Biomedicines, 2021)
Wound healing is a process regulated by a complex interaction of multiple growth factors including fibroblast growth factor 2 (FGF2). Although FGF2 appears in several tissue engineered studies, its applications are limited due to its low stability both in vitro and in vivo. Here, this shortcoming is overcome by a unique nine-point mutant of the low molecular weight isoform FGF2 retaining full biological activity even after twenty days at 37 °C. Crosslinked freeze-dried 3D porous collagen/chitosan scaffolds enriched with this hyper stable recombinant human protein named FGF2-STAB® were tested for in vitro biocompatibility and cytotoxicity using murine 3T3-A31 fibroblasts, for angiogenic potential using an ex ovo chick chorioallantoic membrane assay and for wound healing in vivo with 3-month old white New Zealand rabbits. Metabolic activity assays indicated the positive effect of FGF2-STAB® already at very low concentrations (0.01 µg/mL). The angiogenic properties examined ex ovo showed enhanced vascularization of the tested scaffolds. Histological evaluation and gene expression analysis by RT-qPCR proved newly formed granulation tissue at the place of a previous skin defect without significant inflammation infiltration in vivo. This work highlights the safety and biocompatibility of newly developed crosslinked collagen/chitosan scaffolds involving FGF2-STAB® protein. Moreover, these sponges could be used as scaffolds for growing cells for dermis replacement, where neovascularization is a crucial parameter for successful skin regeneration.
Keywords: scaffold; collagen; tissue engineering; FGF2; chitosan; skin regeneration